Advanced Microsystems for Automotive Applications 2013 Smart Systems for Safe and Green Vehicles - Fischer-Wolfarth, Jan.; Meyer, Gereon; SpringerLink (Online service) (Heidelberg : Springer International Publishing : Imprint: Springer, 2013)
The road vehicle of the future will embrace innovations from three major automotive technology fields: driver assistance systems, vehicle networking and alternative propulsion. Smart systems such as adaptive ICT components and MEMS devices, novel network architectures, integrated sensor systems, intelligent interfaces and functional materials form the basis of these features and permit their successful and synergetic integration. They increasingly appear to be the key enabling technologies for safe and green road mobility. For more than fifteen years the International Forum on Advanced Microsystems for Automotive Applications (AMAA) has been successful in detecting novel trends and in discussing the technological implications from early on. The topic of the AMAA 2013 will be (3z(BSmart Systems for Safe and Green Vehicles(3y(B. This book contains peer-reviewed papers written by leading engineers and researchers which all address the ongoing research and novel developments in the field. www.amaa.des
Driver Assistance and Road Safety -- Networked Vehicles -- Electrified Vehicles -- Energy Efficiency -- Components & Systems.
Keywords: Engineering; Systems engineering; Engineering; Automotive Engineering; Mechatronics; Transportation; Circuits and Systems; Nanotechnology and Microengineering